2021
DOI: 10.3390/antiox10020248
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mitochondrial Dynamics in Parkinson’s Disease—Is 2-Methoxyestradiol a Missing Piece?

Abstract: Mitochondria, as “power house of the cell”, are crucial players in cell pathophysiology. Beyond adenosine triphosphate (ATP) production, they take part in a generation of reactive oxygen species (ROS), regulation of cell signaling and cell death. Dysregulation of mitochondrial dynamics may lead to cancers and neurodegeneration; however, the fusion/fission cycle allows mitochondria to adapt to metabolic needs of the cell. There are multiple data suggesting that disturbed mitochondrial homeostasis can lead to Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 202 publications
(264 reference statements)
0
10
0
Order By: Relevance
“…As molecular pathways of cancer development and cancerogenesis may overlap [ 51 , 52 ], the role of mitochondria in both processes is very interesting. We believe that 2-ME may be a missing link connecting these two pathways [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As molecular pathways of cancer development and cancerogenesis may overlap [ 51 , 52 ], the role of mitochondria in both processes is very interesting. We believe that 2-ME may be a missing link connecting these two pathways [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The induction of oxidative stress is a common factor leading to the development of both neurodegeneration and cancers [ 25 , 55 , 56 ], and one of the mechanisms of 2-ME is the generation of ROS and RNS in many cell lines [ 21 , 22 , 23 , 45 , 54 , 57 , 58 , 59 , 60 ]. The mode of action of many anticancer agents is the induction of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in vitro studies have confirmed the antitumor potential of 2-ME in the treatment of breast, colon and lung cancer [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ]. However, 2-ME did not enter Phase III clinical trials due to the low bioavailability upon oral administration.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous studies, the detailed mode of anticancer action of 2-ME has not yet been fully elucidated. Previously, we have evidenced that from the mechanistic point of view 2-ME induces the expression and nuclear translocation of the neuronal nitric oxide synthase (nNOS) leading to local nitro-oxidative stress and DNA damage, which ultimately results in death of actively dividing cells or carcinogenesis [ 2 , 20 ]. We have further proved that 2-ME at both physiological and pharmacological concentrations induces mitochondrial fission and mitophagy resulting in BAX activation and osteosarcoma cell death [ 21 ].…”
Section: Introductionmentioning
confidence: 99%